Analisa Kelayakan Usaha pada Percetakan Media Print Muara Bulian - Muryati, Muryati; Lubis, Wahya Iffa (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The aim of this research is to assess whether Print Media Printing is feasible or not. If we look at it from a marketing perspective using SWOT analysis, it is found that Media Print is in quadrant I (growth), meaning it is in a state of development and creation. Based on the financial aspect, using payback period analysis shows that this business activity can still be carried out. The rate of return in the future is expected to exceed the level of profit required using the NPV formula to obtain a positive value. The internal rate of return calculation shows that the result is greater than SOCC or the applicable capital interest. Calculation of the profitability ratio (PR) shows that this Print Media Printing business is feasible.